The Caste Connection. On the Sacred Foundations of Social Hierarchy - Jakob De Roover; Sarah Claerhout (Theatrum Historiae)
Today, some commentators argue that the caste system in India is founded in Hinduism; others deny this in the case. This article argues that we do not possess any conceptual apparatus to address this question today, because it was originally raised and answered in a Christian-theological context. The secularization of a Protestant-Christian notion of false religion gave shape to the European conception of ‘the caste system’ as an immoral social hierarchy. Basic theological ideas about the connection between false religion and social practice were transformed into topoi of social theorizing, which constituted the caste system as an experiential entity and conceptual unit in the Western cultural experience of India.